EKSPLORASI TUMBUHAN YANG BERPOTENSI SEBAGAI PENGHASIL MINYAK ATSIRI DI LOMBOK TIMUR-NTB - TIRTA, IG.; AGUS HENDRA WIBAWA, I PT. (Jurnal Biologi Udayana, 2017)
The number of natural biological resources of Indonesia to growing ideas to increase the sale value of plant products especially plant essential oil. Studies of essential plant species that have been common in the market has a lot to do, but for the species of plants are still limited. Exploration is required to get a new species essential oil to be applied to society. Exploration is one of the first steps in this activity to collect the species of plants that have the potential as a producer of essential oils. Exploration conducted in Lombok-NTB April 16 sd May 1, 2014 Acquisition of exploration results as much as 21 numbers were suspected to contain a collection of essential oils. Additional new collections for the Botanical Gardens ‘Eka works’ Bali as much as 2 species.